ABOUT BEAUTY IN RELIGIOUS TEACHINGS (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
The article discusses the teachings of Sufism, that is, mystical beauty and its various aspects are analyzed. Opinions on mystical beauty and the philosophical aspects of the concept of beauty are set out in various religious sources.